Sudut Pandang Masyarakat Kecamatan Cipatujah Kabupaten Tasikmalaya terhadap Pendakwah Perempuan Menurut Perspektif Hadis - Mia Rahmayanti; Amin Iskandar; Fuad Nawawi; Andri Aziz Putra; Dedeh Nur Hamidah (Gunung Djati Conference Series, 2023)
This study aims to discuss the point of view of the people of Cipatujah sub-district, Tasikmalaya district towards female preachers from a hadith perspective. This study uses a qualitative approach by applying the descriptive-analytical method. The results and discussion of this study indicate that the views of the Cipatujah community towards female preachers are in accordance with the perspective of the Sahih Bukhari hadith which is influenced by the customs or habits of the Cipatujah people who use the bandongan method when holding recitations in the community, so that the community can easily understand invitations to da'wah delivered by preachers, but the Cipatujah people's understanding of textual and contextual hadiths is very low because to be able to understand hadith textually and contextually is not only enough with the bandongan method in the recitation process.